Helheim Glacier's Terminus Position Controls Its Seasonal and Inter‐Annual Ice Flow Variability. Issue 5 (24th February 2022) - Cheng, Gong; Morlighem, Mathieu; Mouginot, Jérémie; Cheng, Daniel
Abstract: Over the past decade, one of the largest contributors to total ice discharge across the Greenland ice sheet, Helheim Glacier, has experienced large fluctuations in ice velocity. In this study, we simulate the dynamics of Helheim, from 2007 to 2020, using the Ice‐sheet and Sea‐level System Model to identify the drivers of these large changes in ice discharge. By quantifying the impact of individual external forcing and model parameters on Helheim's modeled velocity, we find that the position of the calving front alone explains the dynamic variability of the glacier, as it has a direct and large impact on Helheim's ice velocity. The seasonal to inter‐annual variability of Helheim Glacier is, however, relatively insensitive to the choice of friction law or ice rheology factor. This study shows that more research on calving dynamics and ice–ocean interactions is required to project the future of this sector of Greenland. Plain Language Summary: At least half of today's mass loss of the Greenland ice sheet is due to the acceleration and retreat of tidewater glaciers. Over the past decade, Helheim Glacier in southeast Greenland has experienced large fluctuations in its flow speed, varying sometimes by more than 2, 000 m/yr within a single year. It is still unclear which physical processes are responsible for the fluctuations in ice speed of Helheim Glacier and how much they contribute individually. In this study, we use a novel numerical technique to simulate Helheim Glacier from 2007 to 2020 to investigate the role of some of the physical processes that have been proposed to potentially drive this variability in ice speed. By comparing the solutions of the numerical model to observations of ice speed, we find that the terminus position is the main control of the ice motion at Helheim Glacier. Key Points: Calving has been controlling Helheim's speed variability since 2007 Averaging the calving rate over 60 days does not change the glacier behavior significantly Constraining a calving law is critical to model the future of Helheim's mass balance